Observational Study of Pulmonary Embolism Patients in Shahid Gangalal National Heart Centre - Rauniyar, B; Adhikari, Chandra Mani; Rajbhandari, R; Limbu, YR; Malla, R; Sharma, R; Rajbhandri, S; Sharma, D; Maskey, A; Singh, SK; Prajapapati, D; Joshi, D; et al. (Nepalese Heart Journal, 2013)
Pulmonary thromboembolism (PE) is a relatively common cardiovascular emergency, with a significant mortality and morbidity often precipitated by deep venous thrombosis (DVT).It is considered as the third most common cardiovascular disorder after Acute Coronary Syndromes (ACS) and Stroke. This study aims to find out the clinical characteristic of Nepali PE patients. We hope that it can be helpful in the early recognition and management of PE patient. Eleven consecutive patients PE who were diagnosed based on CT report were studied. Predisposing factors were same as the other international study. Among eleven patients three were diagnosed as high risk pulmonary embolism, others were intermediate risk. Shortness of breath, chest discomforts are the commonest symptom. Echo revealed Dilated RA and RV were present in all patients. All the patients were treated with Heparin/Low molecular Heparin. Among the three high risk PE patients only one patient was treated with Thrombolytic therapy because of the missed diagnosis. The diagnosis is the most difficult and tricky part in the management of PE as treatment is the easiest part. Early suspicion is the most important part in the management of PE as symptom and sign are non-specific. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 25-28 DOI: http://dx.doi.org/10.3126/njh.v7i1.8498